Mortalidade do Angioedema Hereditário: avaliação da população de um centro de referência - Fernanda Gontijo Minafra Silveira Santos (2021)
Hereditary Angioedema (HAE) is a rare disease that severely affects patients and their families worldwide. It has its origin in excessive local production of bradykinin, which binds to its receptors on the vascular endothelium, leading to angioedema. Consequently, patients present spontaneous edema of the skin and submucosa mainly on the face and limbs, abdominal pain crises, and laryngeal edema. The airways’ involvement can be fatal due to the risk of asphyxiation. This research aims to evaluate the HAE mortality in patients from a referral center in Brazil and their families. Other purposes were to describe the number of deaths that can be attributed to HAE in this population and how many patients had a previous diagnosis. Within this evaluation, assess the life span, characterize the crisis that leads to asphyxia, and factors related to the severity of the laryngeal edema crisis. A cohort of 433 patients from 46 different families was characterized by performing pedigrees and interviews of its members. An observational study was performed with retrospective and prospective components. Detailed information on deaths in patients diagnosed or suspected of HAE was collected using the Brazilian Ministry of Health's Verbal Autopsy. Deaths were classified as due to laryngeal edema or other causes, and their characteristics were evaluated. We analyzed 75 deaths in patients with typical symptoms of HAE. Only 10/75 (13.3%) of the deceased patients had a previous diagnosis. Asphyxia due to laryngeal edema occurred in 39/75 (52%), the highest cause of death even compared to all other reasons added together. The oldest death analyzed was in the 1950s, and ten deaths were observed in the last decade. Five asphyxia deaths were observed in previously diagnosed patients. Sixteen (41%) of the thirty-nine patients who suffered asphyxia did not seek medical help. The time from symptom onset to seeking medical attention had a median of 4 hours and Q1:Q3 of 2.75:9.75 hours. The time until death had a median of 8 hours and Q1:Q3 of 4.0:15.0 hours. In 23.1% of the cases, the original cause of death on the death certificate was allergy/anaphylaxis, and the reason was undefined in 17.9%. Patients who died from laryngeal edema had their life span reduced by 20 years on average compared to patients who died from other causes. The evaluated population still shows a high mortality rate for the disease and a low number of diagnosed patients when observed patients with typical symptoms. HAE mortality is similar to the sum of the ten leading causes of death in the world. Actions such as increasing knowledge of the disease by health care teams, support for diagnosis, and expanding access to the developed treatments are the means to change this scenario. Studies such as mortality assessment can help in directing efforts to improve survival and quality of life.